Effect of dehydration methods on the proximate composition of Halymenia durvillaei - Carino,Ulrica Vilia Lamsen (2007)
ABSTRACT The effect of air oven-drying and freeze-drying methods on the proximate composition (moisture, crude protein, crude fat, crude fiber, ash, total available and soluble unavailable carbohydrates) of Halymenia durvillaei were investigated. The proximate composition of the rehydrated form of the dried seaweed was also determined and compared to that of the fresh form. Results showed that of the dry components of H. durvillaei, the most abundant are total available and soluble unavailable carbohydrates, followed by crude protein and ash. The seaweed has low amounts of crude fiber and crude fat. Freeze-dried samples exhibited higher retention of most of the components of the red seaweed as compared to air oven-dried samples. from the results, it was concluded that H. durvillaei can be a potential good source of dietary fiber, protein and minerals, and that proximate composition of the seaweed is affected by the dehydration methods.